CITY'S PLANNING ERAS: DESIGNING NEIGHBOURHOODS TO PROMOTE PHYSICAL ACTIVITY IN CHILDREN IN SASKATOON. Issue 4 (6th March 2013) - Le, Ha; Muhajarine, Nazeem; ,
Abstract : Objectives: Smart Cities, Healthy Kids (SCHK) is a population-level intervention study examining neighbourhood planning and design on children's physical activity. The general hypothesis of this study, which takes a 'whole-of-a-city' approach to examining urban design, and over the length of time since the city's founding, is that city's planning eras have a varied and measurable effect on children's physical activity. Methods: 1610 Saskatoon children between ages 10 and 14, from 59 residential neighbourhoods were surveyed during elementary school hours from April to June 2010 using the Modifiable Activity Questionnaire for Adolescents (MAQ-A) and a purpose-built survey. Data collected from 1610 children constituted Level 1 (or individual-level) variables. Four eras of neighbourhood designs were assessed in this study: (1) core neighbourhoods that follow a grid-pattern, developed before 1930, (2) fractured grid-pattern neighbourhoods, developed between the 1930s and mid-1960s, (3) curvilinear-pattern suburban development areas, developed between the mid-1960s through to 1998, and (4) mixed curvilinear-pattern neighbourhoods built from 1998 to date. Using two instruments for neighbourhood observation (Neighbourhood Active Living Potential and Irvine-Minnesota Inventory) we measured eight domains of neighbourhood-built environment characteristics: Activity Friendliness, Density of Destinations, Diversity of Destinations, Pedestrian Accessibility, Universal Accessibility, Safety from Crime, Safety from Traffic and Attractiveness. These eight domains and neighbourhood level social variables constituted Level 2 (or contextual-level) variables. Descriptive analysis and multilevel models were used to assess the significant individual and contextual factors associated with children's physical activity. Results: The results showed that 38% of children were considered physically active enough to receive health benefits (>8 kilocalories per kilogram of body weight per day). Children are more physically active in their free play than in their registered activities. At individual level, female children are less physically active than male children; children who reported high scores of perceived walkability of neighbourhoods are more physically active than children with lower score; children of mothers with university degree are more physically active than those of mothers with high school or less education; children from high socio-economic status (SES) families were more active than children from low SES families. At the neighbourhood level, children living in neighbourhoods built in Era 3 (1966–1998) are more physically active than those living in older neighbourhoods (Era 1, 1906–1930). Children from neighbourhoods where the housing affordability was higher had higher level of physical activity than those from neighbourhoods with low housing affordability. Conclusions: Slightly more children in this study reported a level of physical activity that is considered beneficial for health compared with reports from similar studies in Saskatoon in recent years. A mixture of individual and neighbourhood factors were significantly associated with physical activity intensity. Importantly, neighbourhood-built environment, as represented by the neighbourhood design eras, were independently associated with physical activity intensity. Contrary to expectations, children who lived in neighbourhoods that were less dense with curvilinear road network patterns were more intensely physically active compared with more dense, grid-pattern neighbourhoods. Traffic and social safety are likely strong mitigating factors that promotes children's physical activity. Further research is necessary to parse out in detail the complex relationships involved in built environment and physical activity in children.